2004
DOI: 10.1111/j.0141-9838.2004.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil recruitment by ES of Nippostrongylus brasiliensis

Abstract: It has been reported that excretory-secretory (ES) material from the parasitic nematode Nippostrongylus brasiliensis has potential modulatory effects on the host's immune system. We observed that intratracheal instillation of ES from the L3 stage of the parasite reduced neutrophil numbers in LPS-induced inflammation as assessed by bronchoalveolar lavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The literature reveals that both inhibitory and chemoattractant parasite-derived molecules have been described. However, a closer examination of the published data unveiled that tissue-dwelling parasites (usually adults) often release inhibitory factors, possibly in an attempt to reduce the local immune response (Alkarmi and Behbehani, 1989;Culley et al, 2000;Keir et al, 2004;Leid et al, 1987;Lo et al, 1999). Conversely, tissue-migrating larvae usually secrete compounds that promote inflammation (Falcone et al, 2001;Horii et al, 1988;Niwa et al, 1998;Owhashi et al, 1985;Owhashi et al, 1997;Rubio de Kromer et al, 1998;Tanaka et al, 1979;Tanaka and Torisu, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The literature reveals that both inhibitory and chemoattractant parasite-derived molecules have been described. However, a closer examination of the published data unveiled that tissue-dwelling parasites (usually adults) often release inhibitory factors, possibly in an attempt to reduce the local immune response (Alkarmi and Behbehani, 1989;Culley et al, 2000;Keir et al, 2004;Leid et al, 1987;Lo et al, 1999). Conversely, tissue-migrating larvae usually secrete compounds that promote inflammation (Falcone et al, 2001;Horii et al, 1988;Niwa et al, 1998;Owhashi et al, 1985;Owhashi et al, 1997;Rubio de Kromer et al, 1998;Tanaka et al, 1979;Tanaka and Torisu, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Both N. brasiliensis infection [60] and NES alone can inhibit allergen-induced lung inflammation [61]. In vivo studies showed that ES from N. brasiliensis L3 larvae (L-NES) inhibited LPS-dependent neutrophil recruitment to the lungs [62]. Despite the protective effects of NES against lung inflammation, L-NES is intrinsically allergenic [63], suggesting that different components may be acting in opposing manners over the longer term.…”
Section: Functional and Molecular Analyses Of Helminth Productsmentioning
confidence: 99%
“…also identified a neutrophil inhibitory factor (NIF) from Ancyslostoma caninum, which binds CD11b/CD18 and there is a homologue in A. ceylanicum (161,162). Fasciola hepatica is known to secrete a factor that inhibits superoxide output from activated neutrophils (163) and secretory products from L3 of N. brasiliensis (164) also inhibit neutrophil recruitment into the bronchoalveolar lavage.…”
Section: Neutrophilsmentioning
confidence: 99%